(untitled) (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2018)
The purpose of the research is to analyze the management system of service quality and customer satisfaction through the SERVQUAL model in the sugar mills of the Portuguese state during 2016. The study is based on a non-experimental, descriptive transectional design, being the type of field research, supported by a documentary research, with a level of depth in the analysis of evaluative type. Two study universes were identified, the first consisting of the A and B centrals, and the second by their external clients, to whom a Likert-scale questionnaire was applied to collect the information. The results obtained show that the external customers of Central A present an average level of satisfaction since this company does not comply with the characteristics demanded by the client, detecting weaknesses referring to lack of commitment of the organization with the quality management system implemented. On the other hand, the external clients of Central B demonstrate to be satisfied with the perceived quality of service, evidencing a high level of satisfaction. This demonstrates the strengths based on the commitment that all the personnel of the organization have in achieving to satisfy the needs of the client.